2022
DOI: 10.22159/ijap.2022v14i4.44527
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Simvastatin-Loaded Pharmacosomes to Enhance Transdermal Permeation

Abstract: Objective: The objective of the selected study was to design and formulate simvastatin-loaded pharmacosomes and then incorporate into a transdermal patch by solvent evaporation technique to enhance the solubility, bioavailability, and half-life of simvastatin. Methods: Simvastatin comes under the BCS-II class, which has low solubility and high permeability. Simvastain loaded pharmacosomes of six different formulations were prepared by taking simvastatin and soya lecithin in varying ratios and dissolved in a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The low magnitude of relative error, less than±2%, confers the robustness and predictability of software in preparing the stable Favipiravir-loaded PLGA nanoparticles [38,44]. This result indicated that there was no interaction between favipiravir and polymers during the preparation of favipiravirloaded PLGA nanoparticles [22,24].…”
Section: Numerical and Graphical Optimisationmentioning
confidence: 92%
See 2 more Smart Citations
“…The low magnitude of relative error, less than±2%, confers the robustness and predictability of software in preparing the stable Favipiravir-loaded PLGA nanoparticles [38,44]. This result indicated that there was no interaction between favipiravir and polymers during the preparation of favipiravirloaded PLGA nanoparticles [22,24].…”
Section: Numerical and Graphical Optimisationmentioning
confidence: 92%
“…The morphological characteristics of the favipiravir-loaded PLGA nanoparticles were determined by performing analysis using scanning electron microscopy (FEI Quanta 250 FEG, USA). For SEM analysis, favipiravir-loaded PLGA nanoparticles were positioned onto a brass stub and sputtered with gold using gold coating-Quorum, later fixed into a sample holder, then examined under low vacuum (1023 mm HG) and photographed randomly [24].…”
Section: Surface Morphologymentioning
confidence: 99%
See 1 more Smart Citation